Creación de una sala de velación en la ciudad de Ventanas - Zambrano García, Brenchy Edith (2020)
Creation of a veiling room in the Ventanas canton the creation of this venture is born of a problem that is occurring in my canton as an inhabitant I have heard that many residents say because windows being one of the cantons with more inhabitants and movement within the province It does not have a velation room thus creating a positioning with the sole purpose of satisfying the needs of customers. With precedent in the market study it was detected that this service will be recognized however in society they have to adopt other options because there is no place or facilities that opt for an improvement for citizenship. Territorial Resignation aims to encourage the correct procedure and regulations that will be emphasized on this point in an integral way. As a finalization, it can be said that the project will have a positive result in compliance with our proposal